Broiler Litter Ammonia: Caked, Surface and Base Moisture Effects on Emissions - Miles, D.M.; Brooks, J.P.; Adeli, A.; Moore, Jr, P.A. (International Journal of Poultry Science, 2022)
Background and Objective: Relating ammonia (NH3) generation from broiler house bedding to specific management activities is fundamental to developing solutions for NH3 control. Though it is known that increasing litter moisture accelerates NH3 loss, management scenarios specifically for caked litter, litter surface or base moisture have not been considered. The objective of the current study was to determine the variation in NH3 release for caked litter based on bedding age/reuse, to compare sample sizes and surface area of caked litter, as well as evaluate surface and base moisture additions to the litter column. Materials and Methods: A series of laboratory tests were conducted evaluating the caked litter and litter column moisture separately. Daily and cumulative NH3 volatilization was assessed using a chamber acid trap system. Statistical assessments were performed using a mixed linear model to accommodate both the fixed- and random-effects parameters. Results: Caked litter from 0.5 year bedding reuse emitted the most NH3 (new cake), followed by cake formed after more than 3 years of bedding reuse (old cake samples-intact or fragments). Smaller cake samples emitted less than large cake samples. For the litter column, surface misting of litter twice daily emitted the most NH3, followed by surface misting once daily and then the high rate of base moisture addition. Finally, the low rate of base moisture to the litter column and the control with no moisture added were similar. Conclusion: Minimizing cake formation within broiler houses will reduce NH3 emissions once the cake is stored. Management scenarios that prevent litter surface or base wetting, such as proper cooling pad operation and outside drainage away from houses, will reduce NH3 released from litter within broiler facilities. Moisture control in broiler litter and cake can be accomplished with attentive flock management and can reduce NH3 emissions.